Use of Salvage Surgery or Stereotactic Radiosurgery for Multiply Recurrent Skull Base Chordomas: A Single-Institution Experience and Review of the Literature - Yoo, Stella K.; Strickland, Ben A.; Zada, Gabriel; Bian, Shelly X.; Garsa, Adam; Ye, Jason C.; Yu, Cheng; Weiss, Martin H.; Wrobel, Bozena B.; Giannotta, Steven; Chang, Eric L. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Introduction Chordomas are locally destructive neoplasms characterized by appreciable recurrence rates after initial multimodality treatment. We examined the outcome of salvage treatment in recurrent/progressive skull base chordomas.Methods This is a retrospective review of recurrent/progressive skull base chordomas at a tertiary urban academic medical center. The outcomes evaluated were overall survival, progression-free survival (PFS), and incidence of new toxicity.Results Eighteen consecutive patients who underwent ≥1 course of treatment (35.3% salvage surgery, 23.5% salvage radiation, and 41.2% both) were included. The median follow-up was 98.6 months (range 16–215 months). After initial treatment, the median PFS was 17.7 months (95% confidence interval [CI]: 4.9–22.6 months). Following initial therapy, age ≥ 40 had improved PFS on univariate analysis (p = 0.03). All patients had local recurrence, with 15 undergoing salvage surgical resections and 16 undergoing salvage radiation treatments (mostly stereotactic radiosurgery [SRS]). The median PFS was 59.2 months (95% CI: 4.0–99.3 months) after salvage surgery, 58.4 months (95% CI: 25.9–195 months) after salvage radiation, and 58.4 months (95% CI: 25.9.0–98.4 months) combined. Overall survival for the total cohort was 98.7% ± 1.7% at 2 years and 92.8% ± 5.5% at 5 years. Salvage treatments were well-tolerated with two patients (11%) reporting tinnitus and one patient each (6%) reporting headaches, visual field deficits, hearing loss, anosmia, dysphagia, or memory loss.Conclusion Refractory skull base chordomas present a challenging treatment dilemma. Repeat surgical resection or SRS seems to provide adequate salvage therapy that is well-tolerated when treated at a tertiary center offering multimodality care.
Keywords: chordoma; skull base; radiation therapy; surgery; recurrence; Gamma Knife